Methodology in Research on Speech Patterns: Some considerations - Wong, Nicole (Journal of Modern Languages, 2017)
This study considers the concept of methodology, in which the methodology is a term that is used to refer basically to methods involved in testing a hypothesis or finding answers to a research question. The method is the 'how' of the 'what' of the research, i.e. the research question. This article discusses the 'how' of research, that is, the research methodology. It also looks at sampling, the research design, and methods which include data collection, measurement of data and analysis of data.